Developing Speaking Skills Through Folklore Stories In Indonesia Language Learning For Grade V Student SSPF Elementary School 106153 Klambir Lima Kebun Hamparan Perak - Masithah, Irma; Sutikno; Rahmat Kartolo; Heny Triana; Hasnah Harahap, Poppy (PT Inovasi Pratama Internasional, 2026)
This study aims to improve the speaking skills of Grade V students through learning activities based on folktales. The method employed was Classroom Action Research (CAR) conducted in two cycles. Based on the background, the role of Indonesian language teaching in elementary schools, which emphasizes fundamental reading and writing skills, and the use of folktales are vital for enhancing students' speaking abilities. The objectives of this study are: (1) to determine whether folktale-based learning can enhance the speaking skills of Grade I students at UPT SPF State Elementary School 106153 Klambir Lima Kebun, (2) to explore students' motivation during folktale-based learning, and (3) to evaluate the effectiveness of this teaching method in improving classroom interaction. The research method employed was Classroom Action Research (CAR) implemented in two cycles. Each cycle consists of planning, action, observation, and reflection stages. The research findings revealed a significant improvement in students' speaking skills. In Cycle I, the average speaking skill score was 70, with a 60% mastery level (18 out of 30 students achieved the Minimum Competency Standard). After improvements were made in Cycle II, the average score increased to 85, with a 97% mastery level (29 out of 30 students achieved the Minimum Competency Standard). Additionally, students' active participation in the learning process improved, as indicated by the average teacher observation score, which increased from 3.0 in Cycle I to 3.8 in Cycle II. Based on these results, it can be concluded that folktale-based learning is effective in improving the speaking skills of Grade V students. The hypothesis was proven correct: learning through folktales enhances students' speaking skills while fostering their learning motivation and love for local culturev